PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM LQ45 - Shafira, Annisa Prily Bertha; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to test the influence of financial performance, dividend policy, and firmsize to the stock price of the company. The sample of this research is the LQ45 Company which is listed inIndonesia Stock Exchange in 2013-2015 periods. The total sample research in 18 company which has beendetermine by using purposive sampling. And The analysis method has been carried out by using multiple linearregressions analysis. The result of this research shows that: Return on Investment (ROI) does not have anyinfluence to the stock price. It does not have any influence because the profit from the enhancement of the ROI isnot shared but it is used for assets managementactivity; Return on Equity (ROE) has significant and positiveinfluence. The investors consider that the ROE is the measure of profitability in generating optimal profit;Earning per Share (EPS) has significant and positive influence. High EPS will increase the interest of theinvestors, because EPS describe the capability of the company in generating profit on each stock sheet. DividendPayout Ratio (DPR) does not have any influence to the stock price. Because the undistributed profitin the formof dividend will be used for the development of the company in which it is expected that it can increase the stockprice so it generates capital gain; Total Asset (TA) has significant and positive influence. The investors hasassumed that large company is more profitable and it shows that the company is well establishedKeywords: Financial performance, dividend policy, firm size, stock price.